Cover Image, Volume 118, Number 9, September 2017. Issue 9 (13th July 2017) - Priya, R.; Sneha, P.; Rivera Madrid, Renata; Doss, C.George Priya; Singh, Pooja; Siva, Ramamoorthy
Abstract : Cover : The cover image, by R. Priya et al., is based on the Article Molecular Modeling and Dynamic Simulation of Arabidopsis Thaliana Carotenoid Cleavage Dioxygenase Gene: A Comparison with Bixa orellana and Crocus Sativus, DOI:10.1002/jcb.25919 .